2017
DOI: 10.1038/ncomms15630
|View full text |Cite
|
Sign up to set email alerts
|

Rapid mass production of two-dimensional metal oxides and hydroxides via the molten salts method

Abstract: Because of their exotic electronic properties and abundant active sites, two-dimensional (2D) materials have potential in various fields. Pursuing a general synthesis methodology of 2D materials and advancing it from the laboratory to industry is of great importance. This type of method should be low cost, rapid and highly efficient. Here, we report the high-yield synthesis of 2D metal oxides and hydroxides via a molten salts method. We obtained a high-yield of 2D ion-intercalated metal oxides and hydroxides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(169 citation statements)
references
References 50 publications
(76 reference statements)
4
165
0
Order By: Relevance
“…Hasegawa, et al. suggest the possible occurrence of (de)intercalation processes of those cations, similar to the charge storage mechanisms of MnO2 ,. The specific capacitances in aqueous electrolytes are consistent with a previous TiN study (e. g. H 2 SO 4 > KOH > Na 2 SO 4 ) .…”
Section: Resultssupporting
confidence: 86%
“…Hasegawa, et al. suggest the possible occurrence of (de)intercalation processes of those cations, similar to the charge storage mechanisms of MnO2 ,. The specific capacitances in aqueous electrolytes are consistent with a previous TiN study (e. g. H 2 SO 4 > KOH > Na 2 SO 4 ) .…”
Section: Resultssupporting
confidence: 86%
“…To gain insightful understanding of NRR mechanism, it is necessary to design TMNs with simplex structure and stable surface vacancies for the linkage of theoretical models and real‐world catalysts. 2D material has onefold and fully exposed crystal surface, which is widely used as platform for both theoretical calculations and practical applications in electrocatalysis . In the meantime, many works have shown that 2D materials have surface distortion, which can endow 2D materials and their vacancies with excellent structural stability .…”
Section: Exafs Curve‐fitting Results (Error Bounds (Accuracies) Were mentioning
confidence: 99%
“…2D nanomaterials have aroused great interest in both fundamental research and technological applications because of their exceptional physical and chemical properties, distinguishing them from their bulk counterparts, 0D and 1D nanoarchitectures . Over the last decade, an increasing number of 2D materials, including graphene, transition metal dichacolgenides, transition metal oxides, MXenes, etc., have been extensively employed as promising candidates for photocatalysis, electrocatalysis, energy storage and conversion, especially for the next‐generation rechargeable lithium‐ion batteries (LIBs) .…”
Section: Introductionmentioning
confidence: 99%